Laser milling of martensitic stainless steels using spiral trajectories. (April 2017) - Romoli, L.; Tantussi, F.; Fuso, F.
Abstract: A laser beam with sub-picosecond pulse duration was driven in spiral trajectories to perform micro-milling of martensitic stainless steel. The geometry of the machined micro-grooves channels was investigated by a specifically conceived Scanning Probe Microscopy instrument and linked to laser parameters by using an experimental approach combining the beam energy distribution profile and the absorption phenomena in the material. Preliminary analysis shows that, despite the numerous parameters involved in the process, layer removal obtained by spiral trajectories, varying the radial overlap, allows for a controllable depth of cut combined to a flattening effect of surface roughness. Combining the developed machining strategy to a feed motion of the work stage, could represent a method to obtain three-dimensional structures with a resolution of few microns, with an areal roughness S a below 100 nm. Highlights: Micromilling of stainless steel is performed with a fs-pulsed laser. Layers are ablated moving the beam along spiral trajectories. The profile of a single groove is related to process parameters. The depth of cut per layer is studied as a function of process parameters. Areal roughness Sa lower than 100 nm can be attained on the ablated surface.